(untitled) (Diametros, 2009)
The proliferation of ethics committees and ethics consultation services has engendered a discussion of the issue of the expertise of those who provide clinical ethics consultation services. In this paper, I discuss two aspects of this issue: the cognitive dimension or content knowledge that the clinical ethics consultant should possess and the practical dimension or set of dispositions, skills, and traits that are necessary for effective ethics consultation. I argue that the failure to differentiate and fully explicate these dimensions contributes to the confusion over the issue of expertise and fuels, at least partly, the controversies about expertise (or authority) in ethics and the legitimacy of the use of ethical knowledge in clinical ethics consultation.